Stem cell transplantation and regeneration after dorsal root avulsion - Trolle, Carl (Uppsala universitet, Institutionen för neurovetenskap, 2016)
Spinal root avulsion leads to paralysis and loss of sensory function. Surgical methods can improve motor function and ameliorate pain but sensory recovery in adults is poor. Previous studies have shown that cell transplantation or treatment with trophic factors can improve functional outcome in rodents after dorsal root transection or crush. Here, a dorsal root injury model, more similar to human avulsion injuries, was used. The aims of this thesis were to investigate the behaviour of different stem cells following transplantation to avulsed dorsal roots and asses their potential to serve as possible regenerative therapy. In paper I, different murine stem cell types were transplanted to avulsed dorsal roots in rats. Murine embryonic stem cells remained outside the spinal cord and were surrounded by glutamatergic terminals. Boundary cap neural crest stem cells (bNCSC) formed elongated bands outside the spinal cord and migrated to the spinal cord as single cells. In paper II, transplanted bNCSC were further characterized. bNCSC remaining outside the spinal cord expressed glial markers and were associated with different types of sensory fibres. bNCSC that migrated into the injured spinal cord expressed different neuronal markers. In paper III, effects of bNCSC transplantation on local vasculature and glial scar formation were studied. bNCSC increase angiogenesis in a non dose response manner and participate in boundary glial scar formation. In paper IV, bNCSC spinal migration was analysed using two different injury models - dorsal root transection and dorsal root avulsion. In addition, bNCSC capacity to support sensory regeneration was assessed and the results suggest that bNCSC do not support robust regeneration of avulsed afferents. In paper V, an in vitro stem cell model system was used to assess the possibility of using artificial nanomaterials to deliver differentiation factors. Cells treated with either soluble factors or particle-delivered factors showed similar differentiation patterns. Stem cell transplantation offers several opportunities following dorsal root avulsion, including cell replacement and regenerative support. By elucidating the mechanisms by which stem cells can assist regeneration of avulsed afferents will allow for more targeted or combinatorial approaches, including growth factor treatment.